2021
DOI: 10.1038/s41598-021-97016-w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ammonia and hydrogen sulphide as faecal sludge odour control in dry sanitation toilet facilities using plant waste materials

Abstract: On-site dry sanitation facilities, although cheaper than wet sanitation systems, suffer from high malodour and insect nuisance as well as poor aesthetics. The high odour deters users from utilizing dry sanitation toilets as an improved facility leading to over 20% open defecation in Sub-Saharan Africa. To address this malodour concern, this study first assessed odour levels, using hydrogen sulphide (H2S) and ammonia (NH3) as indicators, on two dry sanitation facilities named T1 and T2. The potential of using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Further studies dealt with the role of moringa in addressing water and soil pollution . Indeed, moringa was used in the treatment of sewage sludges, wastewater, effluents, and different types of industrial wastes [ 111 , 137 , 215 , 219 , 229 , 246 , 311 , 391 ]. Studies in this respect, exploiting the potential of M. oleifera seeds as coagulants/flocculants, were carried out in Algeria [ 109 , 111 ], Kenya [ 229 ], Tunisia [ 391 ], Cameroon [ 137 , 140 ], Ghana [ 201 , 215 , 220 ], and Malawi [ 246 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies dealt with the role of moringa in addressing water and soil pollution . Indeed, moringa was used in the treatment of sewage sludges, wastewater, effluents, and different types of industrial wastes [ 111 , 137 , 215 , 219 , 229 , 246 , 311 , 391 ]. Studies in this respect, exploiting the potential of M. oleifera seeds as coagulants/flocculants, were carried out in Algeria [ 109 , 111 ], Kenya [ 229 ], Tunisia [ 391 ], Cameroon [ 137 , 140 ], Ghana [ 201 , 215 , 220 ], and Malawi [ 246 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the first case, the research focuses mainly on the use of biochar to remove unpleasant odors from sanitary toilets and to store liquefied milk fertilizer. Senanu et al [41] while studying the possibilities of using biocarbon covers to remove and suppress the smell of fresh fecal sludge, showed that thermally processed sawdust is able to reduce the reduction of H2S and NH3 by 96.2 and 74.7%, respectively. It was shown that biochar produced from local waste biomass can be a cost-effective and sustainable way to combat odor problems in dry sanitation.…”
Section: Biocover (Surface Application)mentioning
confidence: 99%
“…Odors are generally attributed to the production of various volatile compounds arising from the anaerobic decomposition of fecal matter. The number of complaints regarding odors from outdoor toilets, compost facilities, and livestock farms is increasing year-by-year [1]. Deodorization technologies can be classified into three categories, i.e., technologies employing chemical [2], physical, or biological treatment methods [3].…”
Section: Introductionmentioning
confidence: 99%